Livelihoods, poverty, and food insecurity in Myanmar: Survey evidence from June 2020 to September 2021 - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Key Findings Nine rounds of the Rural-Urban Food Security Survey (RUFSS) have been conducted between June 2020 and September 2021 to assess the impacts of Myanmar’s economic, political, and health crises on various dimensions of household welfare. RUFSS interviews about 2000 mothers of young children per round from urban Yangon, the rural Dry Zone, and recent migrants from these areas. Key Findings ▪ Myanmar has experienced four distinct economic shocks since early 2020. The most recent of these shocks–the spread of the Delta variant–was devastating, with 63 percent of respondents stating that at least one household member had experienced COVID-like symptoms and almost all cases occurring in the May-September 2021 third wave. ▪ 16 percent of interviewed households moved townships between their first interview and September 2021. Around two-thirds of these were from the Yangon sample. ▪ Physical insecurity has emerged as a key impact of political instability, with 53 percent of respondents in September 2021 stating they feel unsafe compared to 37 percent in May 2021. ▪ In September 2021, 48 percent of respondents cited food supply problems (compared to 32 percent in May 2021) and 41 percent cited loss of jobs or income (31 percent in May 2021). Travel restrictions are also more commonly reported. ▪ Job loss has been extremely high in 2021: 28 percent of migrants, 19 percent of urban Yangon households, and 18 percent of rural Dry Zone households reported job loss. ▪ Income-based poverty declined among Yangon households over June-September 2021 (to 44 percent) but remained high among migrants (52 percent) and rural households (58 percent). ▪ Mothers in urban and migrant samples were more likely to have inadequately diverse diets than rural mothers. In Yangon, 44 percent of mothers of young children had poor diets. We also observe very high rates of inadequately diverse child diets in all samples, but particularly a steep rise in inadequate diets between 2020 and 2021 in the rural Dry Zone sample. ▪ To cope with the crisis, households have not only cut back on expenditures but also sold assets (24 percent), taken collateral loans (14 percent), and borrowed money (71 percent) that they say will be difficult to repay. Recommended actions ▪ International donors and local NGOs/CSOs must scale up assistance to Myanmar’s poor through conditional, unconditional, and nutrition-sensitive social protection schemes for vulnerable communities. Further monitoring of the situation in Myanmar will also be essential.